Cardioprotection by Controlling Hyperamylinemia in a "Humanized" Diabetic Rat Model. Issue 4 (21st August 2014) - Despa, Sanda; Sharma, Savita; Harris, Todd R.; Dong, Hua; Li, Ning; Chiamvimonvat, Nipavan; Taegtmeyer, Heinrich; Margulies, Kenneth B.; Hammock, Bruce D.; Despa, Florin
Abstract : Background: Chronic hypersecretion of the pancreatic hormone amylin is common in humans with obesity or prediabetic insulin resistance and induces amylin aggregation and proteotoxicity in the pancreas. We recently showed that hyperamylinemia also affects the cardiovascular system. Here, we investigated whether amylin aggregates interact directly with cardiac myocytes and whether controlling hyperamylinemia protects the heart. Methods and Results: By Western blot, we found abundant amylin aggregates in lysates of cardiac myocytes from obese patients, but not in controls. Aggregated amylin was elevated in failing hearts, suggesting a role in myocyte injury. Using rats overexpressing human amylin in the pancreas (HIP rats) and control myocytes incubated with human amylin, we show that amylin aggregation at the sarcolemma induces oxidative stress and Ca 2+ dysregulation. In time, HIP rats developed cardiac hypertrophy and left‐ventricular dilation. We then tested whether metabolites with antiaggregation properties, such as eicosanoid acids, limit myocardial amylin deposition. Rats were treated with an inhibitor of soluble epoxide hydrolase, the enzyme that degrades endogenous eicosanoids. Treatment doubled the blood concentration of eicosanoids, which drastically reduced incorporation of aggregated amylin in cardiac myocytes and blood cells, without affecting pancreatic amylin secretion. Animals in the treated group showed reduced cardiac hypertrophy and left‐ventricular dilation. The cardioprotective mechanisms included the mitigation of amylin‐induced cardiac oxidative stress and Ca 2+ dysregulation. Conclusions: The results suggest blood amylin as a novel therapeutic target in diabetic heart disease and elevating blood levels of antiaggregation metabolites as a pharmacological strategy to reduce amylin aggregation and amylin‐mediated cardiotoxicity.